ANALISIS PENTINGNYA KEMAMPUAN MENULIS KARYA ILMIAH PADA SISWA SMA - Karim, Andi Rahmatia (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2023)
The aim of this study was to test the significance of scientific writing abilities among secondary school students. The research methodology used involved a literature review, specifically using library research, and adopted a descriptive qualitative approach. The analysis methodology includes a systematic exploration of diverse sources, including books, journals, and research, to understand, evaluate, and synthesize information related to the assessment of scientific writing skills in secondary educational institutions. According to the results of this research, an important component in the Indonesian language curriculum is learning to write scientific papers, which is taught during the secondary education phase. The process of writing a scientific paper is different from writing a regular composition. Achieving accuracy in writing requires the application of certain writing methods and techniques. Improving students' abilities in scientific writing includes several dimensions, including the preparation of the structure of scientific work, the ability to analyze problems and content, proficiency in grammar and spelling, proficiency in writing quotations and bibliography, as well as maintaining accuracy in scientific writing. Mastering writing skills, especially in the context of scientific work, is a complex endeavor with great challenges. Students face challenges in various aspects of scientific writing, including formulating titles, background information, problem statements, discussions, quotations and bibliography, as well as writing formats. Teachers are expected to provide better guidance to students in developing background information, formulating problem statements, building theoretical foundations, solving problems, and creating accurate and appropriate bibliography.